2007
DOI: 10.1093/aje/kwk113
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse, Adult Health, and Health Care Utilization: Results from a Representative Community Sample

Abstract: The long-term consequences of childhood abuse on adult mental health have been a major focus of research. Much less attention has been directed to its effects on physical health outcomes. By use of data from the Ontario Health Survey (n = 9,953), the association between retrospective reports of childhood physical and sexual abuse and adult health and health care utilization was examined in men and women. The population health survey was conducted from November 1990 to March 1991 in the Canadian province of Ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 50 publications
7
106
1
8
Order By: Relevance
“…However, much of the research on this issue has focused on long-term consequences such as adult mental health, physical health and health care utilization. In this research, CSA has been shown to be associated with psychological disorders such as depression (Molnar, Buka, & Kessler, 2001), post-traumatic stress disorder and anxiety disorder (Chen et al, 2010) and borderline personality disorder (Chartier, Walker, & Naimark, 2007). These negative mental health outcomes have been shown across all age groups.…”
Section: Section 1: Introductionmentioning
confidence: 78%
“…However, much of the research on this issue has focused on long-term consequences such as adult mental health, physical health and health care utilization. In this research, CSA has been shown to be associated with psychological disorders such as depression (Molnar, Buka, & Kessler, 2001), post-traumatic stress disorder and anxiety disorder (Chen et al, 2010) and borderline personality disorder (Chartier, Walker, & Naimark, 2007). These negative mental health outcomes have been shown across all age groups.…”
Section: Section 1: Introductionmentioning
confidence: 78%
“…Among women with SMI, 43-52% report a history of childhood sexual abuse and 33-52% report a history of childhood physical abuse (e.g., Cloitre et al, 1996;Muenzenmaier et al, 1993;Mueser et al, 1998;Rosenberg et al, 2007), compared to 13-32% and 20-21%, respectively, among women in the general population (Briere and Elliot, 2003;Chartier et al, 2007;Edwards et al, 2003;Finkelhor et al, 1990). Many fewer studies have examined the prevalence of childhood abuse among men.…”
Section: Introductionmentioning
confidence: 99%
“…These findings, in conjunction with findings from Chartier et. al., 8 Paranjape et. al., 18 and Henning et.…”
Section: Discussion Prevalence and Sociodemographic Correlatesmentioning
confidence: 99%
“…4 Recent studies on sexual assault have documented not only the immediate health consequences of the assault, but how injuries and psychosocial stressors experienced during the assault can lead to chronic medical conditions, including smoking, alcohol abuse, chronic pain syndromes, asthma, heart disease, and arthritis among victims. [5][6][7][8][9][10] Few studies, however, have documented the associations between sexual assault and unhealthy behaviors in population-based studies. Additionally, it is unclear how the experience of sexual assault may be associated with health-care utilization trends outside the immediate post-assault time period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation